2020
DOI: 10.2174/1874210602014010211
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Treatment in Pregnancy: Knowledge, Attitudes, and Practices of Dentists and Interns in Jeddah, Saudi Arabia

Abstract: Aim: Pregnant women require special consideration in dental treatment due to physiological changes during their pregnancy. The aim of this study is to assess the knowledge, attitudes, and practices of dentists and dental interns in Jeddah, Saudi Arabia, regarding endodontic treatment during pregnancy. Methods: A cross-sectional study was conducted using validated self-report questionnaires completed by 450 dental interns and dentists who treat pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The proportion of patients who had not yet acquainted with the concept of endodontist was much more than we expected. We believe that this was due to the fact that patients were unaware of endodontics 2,20 . In previous studies, the most important criterion for patients was the skill and experience of the staff 6,8,21 , which we noticed, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients who had not yet acquainted with the concept of endodontist was much more than we expected. We believe that this was due to the fact that patients were unaware of endodontics 2,20 . In previous studies, the most important criterion for patients was the skill and experience of the staff 6,8,21 , which we noticed, too.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the participants reported their endodontics treatment done before. Previous studies revealed that the patient-dentist relationship strongly affects a patients' feeling to be safe and secure 19,20 . Therefore, practitioners should explain the course of the treatment to patients, including alternative treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the ignorance of the patient may mirror that of their dentist. A wide-ranging literature review highlighted the global issue relating to the awareness of dental practitioners and the use of imaging techniques in pregnant women; their knowledge, as well as that of their students and interns, has been shown by several researchers to be substandard (22)(23)(24) . For instance, 67% dentists were found to believe that periapical radiographs could only be acquired safely in the second stage of pregnancy; panoramic radiographs were deemed to be contraindicated by 69% (23) .…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature review revealed that there is a worldwide concern about dentists' knowledge regarding dental imaging during pregnancy. Several studies have revealed that the knowledge of dental students, interns, and dentists on ionizing radiation and radiation protection is very poor [6,8,9,[20][21][22]. In a study by Aboalshamat et al, 67% of dentists considered periapical radiographs safe only during the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Aboalshamat et al, 67% of dentists considered periapical radiographs safe only during the second trimester. Panoramic radiographs were considered contraindicated during pregnancy by 69% of the participants [ 21 ]. Bedre and Sharma found that only 2% of dentists knew that dental imaging is safe in all trimesters and 44% thought it was unsafe in all trimesters [ 20 ].…”
Section: Discussionmentioning
confidence: 99%